WORDWALL GAMES BASED MEDIA TO IMPROVE STUDENTS ' LEARNING OUTCOMES - Devia Ramadani; Jamilah; Arik Darojat (Institut Pendidikan Indonesia, 2024)
Low learning outcomes are one of the big problems in the learning process, this can be caused by various factors including a lack of innovation in choosing learning media which can make learning less interesting and result in reduced student motivation. In this digital era, the application of wordwall games-based media will improve student learning outcomes in Civics learning. However, there are no empirical studies that show that this can increase students' learning motivation so that it can influence learning outcomes. There were 30 participants in this research who were class X students at SMAN 15 Garut. This research uses a pre-experimental method with a One Group Pre-Test and Post-Test Design research design. The research instruments used were pre - test, post - test and questionnaire. The research results show that (1) Implementation wordwall games - based learning media for class _ (2) There is an increase in student learning outcomes before (pretest) and after ( post - test ) the application of wordwall games -based learning media This research also shows that there is a difference in improvement in the achievement of student learning outcomes after implementing wordwall games . With the average value of the normalized gain score being 0.75, the interpretation is classified as high. (3) The relationship between the application of wordwall games- based learning media to student learning outcomes in Civics learning in Class X11 SMAN 15 Garut is obtained . The Sig (2-tailed) value is 0.000 <0.05, which means there is a significant correlation between variables X and Y. Furthermore, it is known that the calculated r value for the relationship between variables X and Y is 0.804 > r table 0.361 . By interpreting the assessment, the correlation coefficient was found to be 0.804 , which is included in the